Evolutionary correlations in flavonoid production across flowers and leaves in the Iochrominae (Solanaceae). (October 2016) - Berardi, Andrea E.; Hildreth, Sherry B.; Helm, Richard F.; Winkel, Brenda S.J.; Smith, Stacey D.
Abstract: Plant reproductive and vegetative tissues often use the same biochemical pathways to produce specialized metabolites. In such cases, selection acting on the synthesis of specific products in a particular tissue could result in correlated changes in other products of the pathway, both in the same tissue and in other tissues. This study examined how changes in floral anthocyanin pigmentation affect the production of other compounds of the flavonoid pathway in flowers and in leaves. Focusing on the Iochrominae, a clade of Solanaceae with a wide range of flower colors, liquid chromatography coupled with mass spectrometry and UV detection was used to profile and quantify the variation in two classes of flavonoids, anthocyanins and flavonols. Purple, red, orange and white-flowered Iochrominae produced all of the six common anthocyanidin types, as well as several classes of flavonols. Differences in anthocyanin and flavonol production were significantly correlated in flowers, particularly with respect to B ring hydroxylation pattern. However, these differences in floral flavonoids were not strongly related to differences in leaf chemistry. Specifically, most species made only flavonols (not anthocyanins) in leaves, and these comprised the two most common flavonols, quercetin and kaempferol, regardless of the color of the flower. These results suggest that shifts in flower color may occur without significant pleiotropic consequences for flavonoid production in vegetative tissues. Similar studies in other systems will be important for testing the generality of this pattern in other groups of flowering plants. Graphical abstract: Correlated shifts in dihydroxylated and trihydroxylated flavonoids were found in flowers of nine Iochrominae species, but these changes were not strongly related to differences in leaf flavonoids. Highlights: Correlated shifts in di-, trihydroxylated flavonoids found in Iochrominae flowers. Shifts in floral flavonoids are not related to differences in leaf flavonoids. Leaves produce quercetin and kaempferol regardless of the floral flavonoid signature.